Evaluation of Physicochemical On-Farm Quick Tests for Estimating Nutrient Concentrations in Pig Slurry and Development of an Application for Mobile Devices - Max-Frederik Piepel; Klaus Dittert; Hans-Werner Olfs (Agronomy, 2022)
Farmers need to know the actual nutrient concentrations in organic manures in order to enable optimal crop nutrition and to avoid nutrient losses into the environment. Physicochemical quick tests offer a way to estimate nutrient concentrations on a farm but require statistical calculation models to be applied by the farmer. A total of 391 pig slurries, were sampled from practical farms in northwest Germany and ammonium nitrogen (AN), total nitrogen (TN), total phosphorus (TP), total potassium (TK) concentrations, and dry matter were analysed in a laboratory. Furthermore, on-farm quick tests were used to determine electrical conductivity and specific density (SG) and the ammonium concentration with a Quantofix-N-Volumeter. Simple and multiple linear regression models for all lab analysed nutrients and on-farm determined parameters were calculated. The best regression models for all slurries were found for AN based on Quantofix-N-Volumeter (R2 = 0.92), TN based on Quantofix-N-Volumeter, and dry matter (R2 = 0.95), TP based on dry matter (R2 = 0.88), and TK based on Quantofix-N-Volumeter (R2 = 0.70). An application for mobile devices is being developed that will allow farmers to use these statistical models in a user-friendly way. Future regression models from other studies might be integrated into the app database so that farmers can calculate nutrient concentrations in pig slurries based on regionalised data.